Teaching mental skills for sport - Archer, Mark; Gould, Daniel; Virtual Brands ([Wilbraham, Mass.] : Virtual Brands, 2001)
Sport psychology consultant, Daniel Gould, provides instruction in mental training exercises for athletes
Title from title screen
Executive producers: Britt Brewer, Al Petipas, Judy Van Raalte ; camera, Geoff Alson, Mark Archer, Wendy Wong
Host: Al Petitpas
Consultant: Daniel Gould
Keywords: Sports -- Psychological aspects; Athletes -- Psychology